PENGARUH PENGHARGAAN FINANSIAL, PERTIMBANGAN PASAR KERJA, NILAI INTRINSIK PEKERJAAN DAN PERAN GENDER TERHADAP KARIR AKUNTAN PADA MAHASISWA AKUNTANSI UNIVERSITAS INTERNASIONAL BATAM - Lingga, Dinda Deritani Susanti; Nopiana, Puspita Rama (SCIENTIA JOURNAL, 2019)
The purpose of this study was to determine the factors that influence the selection of accountant careers at accounting students of Batam International University. Independent variables used are financial rewards, labor market considerations, intrinsic value of work and gender roles. The dependent variable used is the accountant career. Data analysis techniques in this study include multiple linear regression. The results of the study can be seen that the variables of financial rewards in accountant career selection with t count 0,161 are smaller than t table 1,665 and a significant value of 0,872 <0,05. Job market consideration variables in accountant career selection with 2,704 t count smaller than t table 1,665 and significant value 0,008 <0,05. the variable intrinsic value of work in the accounting career selection with t count 1,144 is smaller than t table 1,665 and significant value is 0,256 <0,05.